Beneath the American Renaissance: The Subversive Imagination in the Age of Emerson and Melville - Reynolds, David S (Oxford University Press, Incorporated, 2011)
Since its initial publication, David Reynolds's Beneath the American Renaissance has become a seminal resource for understanding American literature. It ranks alongside classics like F.O. Matthiessen's The American Renaissance, R.W.B. Lewis's The American Adam, and Eric Sundquist's To Wake the Nations as a book that defined how we apprehend our literary past. With its combination of sharp critical insight, engaging observation, and narrative drive, it represents the kind of masterful cultural history for which Reynolds is now known. Now back in print in an affordable paperback edition that includes a new foreword by Sean Wilentz that recollects the book's impact and influence, a lost gem returns. It is poised to find an appreciative new readership in anyone interested in the genesis of America's most significant literary epoch and the iconic figures-Hawthorne, Whitman, Dickinson, and Melville-who defined it.